Pigment characterization and lovastatin content of Monascus purpureus isolates - ERNAWATI KASIM; SRI ASTUTI; NOVIK NURHIDAYAT (Biodiversitas Journal of Biological Diversity, 2005)
Research on characterization of pigment and lovastatin content of M. purpureus had been done. The aim of the research was to select 19 isolates of M. purpureus which produced the highest lovastatin content, and whether there was any correlation between pigment content and the lovastatin content. The isolates were grown on slant agar of bean sprout extract agar for 14 days. The spores suspension was inoculated to sterile cooked rice IR 42, then incubated for 14 days at 27-32oC. The fermented rice called â€œangkakâ€, dried in oven at 40-45oC for two weeks. The dried â€œangkakâ€ was powdered to measure the content of the pigment and lovastatin. By using spectrophotometer the content of the yellow pigment and the red pigment at 390 nm and 500 nm wavelength respectively, could be detected. The content of lovastatin could be measured by using HPLC. The result showed that all the tested isolates could produce lovastatin compound, the yellow and the red pigment. The highest lovastatin content was 0.92% which produced by JmbA isolate. There was no correlation between the pigment and the lovastatin content. Key words: Monascus purpureus, pigment, lovastatin.